What effects of COVID-19 on regional economic resilience? Evidence from 31 provinces in China - Meng, Tian; Tian, Congying; Zhang, Henglong; Koo, Chun Kwong (Frontiers in Public Health, 2022)
After the 2008 global financial crisis, more and more scholars began to pay attention to economic resilience. In 2020, the outbreak of COVID-19 made the public aware of the importance of regional economies to resist and adapt to external shocks. In this study, we introduce the concept of regional economic resilience to analyze the resistance of China's regional economy under COVID-19 pandemic, and explore what factors affect the response of regional economy to external shocks. The analysis reveals significant differences between the COVID-19 pandemic and the 2008 financial crisis in terms of impact types and influencing factors. We find that developed provinces have more vulnerable regional resilience, and they are more susceptible to the epidemic in the early stages of the shock, in which government power and social environment play an important role in shaping regional resistance. This paper complements the lack of studies on regional economic resilience under external shocks, arguing that not only the known economic structure factors, but also the social inheritance structure and the fundamental strength of government can significantly affect the resilience of regional economies to shocks under COVID-19. The study suggests that the unique nature of COVID-19 as a shock itself needs to be carefully considered when exploring the determinants and outcomes of regional economic resilience.